Meningkatkan Hasil Belajar Materi IPS Melalui Model Pembelajaran Direct Instruction Dengan Pendekatan Scientific - Abdullah, Rahmat (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
Abstract. This study aims: (1) To improve the learning outcomes of social studies material through direct instruction learning models with a scientific approach, class VII4 students of SMPN 1 Tanete Rilau, Barru Regency. (2) To find out the percentage of completeness in learning social studies material, class VII4 students of SMPN 1 Tanete Rilau, Barru district. (3) To determine changes in the teacher's ability to manage and control direct instruction learning models with the scientific approach. (4) To find out the change in activity students carry out direct instruction learning models with the scientific approach. This research was conducted in three cycles. Each cycle consists of four stages of activities which include: (a) Stage of planning (planning), (b) stages of implementation of actions (acting), (c) stages of observation (observing) and (d) reflection stage (reflecting). The subjects of this study were 31 female respondents of all types. Qualitative data on student activity and teacher ability, while quantitative data on learning outcomes per cycle. The results of the study show that: (1) the learning outcomes of the IPS material, the difference in average increases by 12.26, increases in the category of less than good from cycle two to cycle three. (2) The percentage of completeness in studying social studies material reached 90.32% in the third cycle. (3) Changes in the ability of teachers, increasing the score of the percentage difference of 20%, increasing the category enough to be good. (4) Changes in the activity of students increased by a score of 10% difference in percentage, an increase in the category to be good enough